Geografi (Kesejarahan) Dan Arsitektur (Lansekap) Sebagai Ilmu Bantu Arkeologi (Sebuah Uraian Singkat) - Sugeng Riyanto (Balai Arkeologi Yogyakarta, 1995)
In its long journey, archeology as a science has long since left artifact-oriented studies (including features and ecofacts) oriented. The three of them are no longer seen as individual data that must be studied individually, but are seen as part of the overall archaeological data in a certain spatial scale. This does not mean that artifacts, features, ecofacts, no longer need to be studied individually, but this study is the beginning of the totality of archaeological research. Furthermore, it is developed, by taking into account the matrix, location and context, it is also necessary to pay attention to environmental and spatial conditions at a certain scale: from micro to regional, or more broadly.